Atypical Presentation of Spontaneous Bilateral Internal Carotid Artery Dissection Leading to Stroke: A Case Report - Bao Liao; Qin Yang; Dengxing Li; Chai Theam Ooi (Clinical Medicine Insights: Case Reports)
A case of spontaneous bilateral internal carotid artery dissection (ICAD) in a 36-year-old male, potentially linked to COVID-19, is reported. Initially presenting with excessive daytime sleepiness, an atypical symptom for ICAD, the patient lacked focal neurologic deficits. Diagnostic evaluation revealed severe stenosis and dissecting aneurysms in both carotid arteries. Treatment included anticoagulation, corticosteroid therapy, and subsequent endovascular stent placement. This case underscores the importance of considering ICAD as a potential complication of COVID-19, especially in patients with atypical symptoms. Further research is needed to understand the underlying mechanisms and optimize treatment strategies.